2005
DOI: 10.1029/2005gl024701
|View full text |Cite
|
Sign up to set email alerts
|

The response of the Southern Annular Mode, the East Australian Current, and the southern mid‐latitude ocean circulation to global warming

Abstract: Climate models predict an upward trend of the Southern Annular Mode (SAM) in response to increasing atmospheric CO2 concentration, however the consequential impact of this change on oceanic circulation has not been explored. Here we analyse the outputs of a series of global warming experiments from the CSIRO Mark 3 climate model. We show that although for the zonal wind stress change the maximum is located at approximately 60°S, in terms of the change in surface wind stress curl, the maximum is situated at app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
249
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(269 citation statements)
references
References 16 publications
14
249
0
6
Order By: Relevance
“…The rainfall tends to be enhanced by a warmer surface, similarly to changes off South Africa simulated by Reason and Mulenga (1999). Cai et al (2005) examined these SST patterns in the late 21st century climate from Mk3 and suggested that the anomalies may be consistent with a change in the oceanic circulation. They showed that the simulated change in the curl of the wind stress on the ocean surface should theoretically drive a spin-up of the entire Southern Ocean circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The rainfall tends to be enhanced by a warmer surface, similarly to changes off South Africa simulated by Reason and Mulenga (1999). Cai et al (2005) examined these SST patterns in the late 21st century climate from Mk3 and suggested that the anomalies may be consistent with a change in the oceanic circulation. They showed that the simulated change in the curl of the wind stress on the ocean surface should theoretically drive a spin-up of the entire Southern Ocean circulation.…”
Section: Discussionmentioning
confidence: 99%
“…If the SAM continues to become increasingly positive, in particular during the summer (Fyfe et al, 1999;Kwok and Comiso, 2002;Thompson and Solomon, 2002;Marshall, 2003;Renwick, 2004;Cai et al, 2005), the conditions such as those described in Figure 10 would tend to become more frequent even when the relation between SAM and blocking in the SA is not straightforward, triggering future possible large-scale events where the potential of further transitioning cases may be enhanced. However, it is also worth mentioning that at least during the SH spring time the positive trend in the SAM is at least partially expected to decrease as the stratospheric O 3 levels gradually recover (Shindell and Schmidt, 2004).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…As discussed in the next paragraphs, high-latitude activity can be seen to be a precursor of Catarina's development. In addition, the trend to more positive SAM under global warming and ozone losses (Fyfe et al, 1999;Kwok and Comiso, 2002;Thompson and Solomon, 2002;Marshall, 2003;Renwick, 2004;Cai et al, 2005) suggests an increase in such blocking events. Figure 7 shows the time series (every 6 h) of the BI and the EVWS superimposed on the regional and hemispheric AAO indices.…”
Section: The 'South Atlantic Index' and High-latitude Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the associated trans-Pacific tilt of the near-equatorial oceanic thermocline (Bjerknes 1966) can be expected to lessen, and the coupled Pacific oceanatmosphere system to become more chronically ''El Niño''-like (Quinn 1974;Wyrtki 1975) in its underlying mean background state. Climate change is also predicted to drive a strengthening of the EAC itself and a general southward shift of the South Pacific Gyre (Cai et al 2005, Steinberg 2007), of which the EAC represents the far western limb. Effects on local ecosystems are expected to be influenced in two potentially opposing ways by an intensification of EAC flow adjacent to the Capricorn Eddy.…”
Section: The Implications Of Climate Change For Eddy-related Effectsmentioning
confidence: 99%